2000
DOI: 10.1007/s005950070006
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Upper Dorsal Thoracoscopic Sympathectomy on the Total Amount of Body Perspiration

Abstract: Thoracoscopic T2-T3 sympathectomy is the treatment of choice for primary palmar hyperhidrosis (PPH); however, compensatory hyperhidrosis (CH) is a disturbing sequela of this operation, the mechanism of which is poorly understood. This study was conducted to evaluate the effect of heat stress on total body perspiration after thoracoscopic T2-T3 sympathectomy, and determine its correlation with CH. A total of 17 patients with PPH who underwent bilateral T2-T3 sympathectomy were subjected to heat stress induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
(23 reference statements)
0
10
1
Order By: Relevance
“…They suggested that the increased sweating in other parts of the body occurring after surgery compensated the abolition of palmar perspiration. On the other hand, Kopelman et al [10] found no correlation between the preand post-sympathectomy amounts of total body perspiration. They thus questioned the compensatory nature of increased perspiration in other areas of the body developing after sympathectomy.…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that the increased sweating in other parts of the body occurring after surgery compensated the abolition of palmar perspiration. On the other hand, Kopelman et al [10] found no correlation between the preand post-sympathectomy amounts of total body perspiration. They thus questioned the compensatory nature of increased perspiration in other areas of the body developing after sympathectomy.…”
Section: Discussionmentioning
confidence: 97%
“…The opposite effect, namely reduced sweating in other parts of the body -not those affected by the sympathectomy, has also been reported [8,20]. A recent study [24], which examined the correlation between the amount of compensatory hyperhidrosis and the total amount of pre-and postoperative body perspiration, found no correlation between them. The mechanism of compensatory hyperhidrosis thus appears to be more complex than simple compensation for thermoregulatory purposes, and remains obscure.…”
Section: S Evaluation Based On Postoperative Sequelsmentioning
confidence: 89%
“…2,13,15 It has been suggested that the severity of RS is highly associated with the number of denervated segments or resected ganglia, and the severity of RS may change FIGURE 1. [16][17][18] According to several reports on RS, 5,14-16,18 there is a wide variation for RS rates among the different techniques that are used to treat patients with PH. A Ushaped endoclip is suitable for clipping along with suture sling, retrieving, and pulling back (unclipping).…”
Section: Discussionmentioning
confidence: 99%